A inclusão das pessoas com deficiência na comunidade: o direito à moradia e as barreiras que impedem a sua efetivação - Arantes, Maristela Lugon (2017)
The research aims to identify the barriers that impede the right of people with disabilities to decent housing. The UN Convention on the Rights of Persons with Disabilities (CRPD), ratified by Brazil in 2008 and the Brazilian Inclusion Law (LBI - Law 13,146 / 15) recognize the right of these persons to make choices on all aspects of their Life, including in relation to their dwelling. The CRPD innovates by breaking the paradigm of the disabled person as incapable of performing tasks and managing their own lives, delegating to them that they take the place of protagonist of their existence. The empowerment of these people, so that they achieve autonomy and independence, here dealt with under the focus of intervention bioethics, is the main objective of the CRPD. However, the many physical and attitudinal barriers imposed on them make the realization of these rights slow and complex. In order to do so, the context of the Inclusive Residences in the city of Vitória - ES, where adults with disabilities are living, was taken from the extinct Unit of Attention to the Disabled (UNAED), which operated in a similar model to the Institutions, portrayed by Goffman and Foucault. It was concluded that the Inclusive Residences in the ES, established in the legal molds and located in noble neighborhoods, provoke negative reactions of the local communities, who are mobilized in order to prevent their permanence there. The methodology used was the bibliographical research, besides the search in public documents, reports, lawsuits and in articles published in newspapers and Internet pages. It should be noted that all the photographs used in the survey were taken from newspapers, internet pages and magazines of free access to the public. In a brief comparison between the before and after, it was observed to show the sensible improvement in the life of the graduates of the UNAED, with the new routine within the community. It was concluded that, in addition to physical barriers such as lack of accessibility, which hinders or prevents disabled people from accessing goods and services, attitudinal barriers such as prejudice, discrimination and intolerance are the most difficult to combat , Because they are accomplished by often subtle attitudes, but that have devastating effects on the lives of people with disabilities. These attitudes are passed on from generation to generation through unprecedented repetitions, which naturalize the inequality of vulnerable groups, as we analyze. In this context, public policies to raise awareness about social inclusion, based on the ethics of alterity and worked on in order for the community to understand the meaning of human diversity and its importance, are presented as an alternative for the inclusion of people with disabilities in society.